LINGUOCULTURAL FEATURES OF IDIOMS AND PROVERBS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines the linguocultural nature of idioms (phraseological units) and proverbs, their role in reflecting national culture, their function within the conceptual system, and their significance in literary and oral discourse. The study analyzes the role of linguistic units in preserving cultural codes as well as their lacunar characteristics in translation.